Red fruit oil increases trophoblast cells and decreases caspase-9 expression in placenta of lead exposed mice - Sumarsono, Portia; Widjiati, Widjiati; Susilowati, Suherni (Faculty of Medicine, Trisakti University, 2016)
BACKGROUNDLead is able to pass through the placental barrier and interfere with fetal development. Red fruit has high antioxidant activity, due to carotenoids (pro-vitamin A), tocopherols (vitamin E) and unsaturated fatty acids. This study aims to examine the effect of red fruit oil towards placenta in pregnant mice before lead exposure.METHODSThis was a laboratory experimental post test only study, using 20 pregnant mice (Mus musculus) that were randomized into five groups. The negative control group was not exposed to lead; intervention group 0 (P0) was exposed to lead at 0.011 mg/20 g BW/day on days 6-15 of gestation. The intervention groups P1-P3 were given red fruit orally at 0.3 mL/20 g BW/day, 0.8 mL/20 g BW/day, 0.9 mL/20 g BW/day, respectively, before lead exposure. Normal trophoblast cell count and caspase-9 expression of trophoblasts were calculated. One-way ANOVA, Kruskal-Wallis and Mann Whitney tests were used to analyze the data.RESULTSThe intervention groups P2 and P3 given red fruit at 0.8 mL/20 g BW/day and 0.9 mL/20 g BW/day showed a significant increase in normal trophoblast cell count of 88.2% (p=0.024) and a decrease in caspase-9 expression of 70.8% compared with P0 to which was not given red fruit (p=0.020). CONCLUSIONRed fruit increased normal trophoblast cell count by 88.2% and decreased caspase-9 expression by 70.8% in pregnant mice before lead exposure. It should be noted that red fuit may prevent oxidative damage to cells.